Creativity: the Actor in Performance - Trenos, Helen (De Gruyter, 2014)
Creativity: The Actor in Performance focuses on what it takes to be a creative performer. Many stage-actors succeed in rehearsals, yet under-perform where it counts-in performance. But, as actors know, performance is a thing unto itself-something is going to have to happen out there beyond anything that happened in rehearsals. This book provides actors, their teachers and directors with insights into the creativity of the actor in performance. An historical account of the emergence and development of one of the most generative concepts of our times - creativity - provides a theoretical backdrop to a critical discussion of the creativity of acting - a discussion that includes analyses of Denis Diderot, George Henry Lewes, William Archer, Konstantin Stanislavsky, Michael Chekhov, Michel Saint-Denis, Zeami and Eugenio Barba. Creativity: the actor in performance concludes by offering a detailed rationale for performance-oriented actor training, offering examples of workshop exercises (CREATICS) which focus on developing four main competencies crucial for successful and creative performances: situation awareness, audience awareness, divided consciousness and presence.